NMR studies of a DNA containing 8-hydroxydeoxyguanosine. - Oda, Y (1991)
The effects of hydroxylation at the C8 of a deoxyguanosine residue in DNA were studied by NMR analysis of a self-complementary dodecanucleotide, d(C1-G2-C3-oh8G4-A5-A6-T7-T8-C9-G10-C11-G12), which has an 8-hydroxy-2'-deoxyguanosine (oh8dG) residue at the 4th position. NMR data indicate that the 8-hydroxyguanine (oh8G) base takes a 6,8-diketo tautomeric form and is base-paired to C with Watson-Crick type hydrogen bonds in a B-form structure. The thermal stability of the duplex is reduced, but the overall structure is much the same as that of the unmodified d(CGCGAATTCGCG) duplex. The structural changes caused by 8-hydroxylation of the deoxyguanosine, if any, are localized near the modification site.